PELAKSANAAN UNSUR-UNSUR PERLINDUNGAN KONSUMEN JASA TRANSPORTASI UDARA (STUDI KASUS DI BANDARA ADISUCIPTO YOGYAKARTA) - , Delonix Windy Perwitasari, SE, Dina W. Kardiomedjo, SH, LLM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the implementation of consumer protection elements of air transport services, its constraints and how to overcome obstacles related to safety and aviation security aspects, passenger service aspects, and aircraft maintenance aspect in Adisucipto Airport of Yogyakarta. The research was carried out by the method of empirical and approaches juridical, as such Ordinance Air Transportation 1939, Law No. 15 of 1992, Law No. 8 of 1999, Law No. 1 of 2009, and Goverment Regulation No. 40 of 1995. The research was conducted in Adisucipto Airport of Yogyakarta,with personnel at PT Angkasa Pura I of Yogyakarta, and consumers passenger were dissatisfied with the airport services because its lack of safety and aviation security aspects, passenger service aspects, and aircraft maintenance aspects. The results indicate that the implementation of consumer protection elements of the air transportation service in Adisucipto Airport of Yogyakarta in terms of safety and aviation security aspects, passenger service aspects, and aircraft maintenance aspects, has been carried out by the airline in accordance with statutory regulations. How ever, there are constraints that occur within this problem comes from consumers, airport and airlines management, and the government. How to overcome the constraints that there, Consumers to report to need the airport management for any inconvenience at the airport, for airport and airlines management must give more attention to consumer in the aspect of inflight service, the government must take action against consumers, airport and airlines management who violate the safety and aviation security aspects.